Situation Report: Albania, 16 March 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The "Open Letter" Still Actual / by Louis Zanga Steps against Pollution / by Louis Zanga Tirana-Prishtina Air Route / by Louis Zanga Albanian-North Korea Trade Agreement / by Louis Zanga About the Stalin Issue / by Louis Zanga